Defiant daughters dancing three independent women dance - Corpus, Rina Angela P. (Quezon City University of the Philippines Press, 2007)
Rina Angela Corpus performs a tricky step in this project of telling the story of Philippine contemporary dance, notating its movement against the grain of programmatic choreography. First, she challenges the manner in which histories of dance are crafted from a perspective that precludes the personage of woman as a productive agent in the invention of the art. Second, she takes exception to this historiography by exercising her own form of inclusion and enlistment, foregrounding the practice of three women dance makers who have striven to remake the institution of dance itself and the subjectivities of its faithful. In enacting this complicated turn of the body against the gravity of its tradition, Corpus contrives the argument of independence and its logic of defiance."--Foreword.
Foreword/Moving / Patrick D. Flores -- Preface -- Introduction/A personal movement : dissident gestures into dance -- Chapter 1. Women and dance in society -- Chapter 2. Defying and defining : feminist dance histories of independent women dance-makers -- Chapter 3. Generations and genealogies : women in Philippine ballet and modern dance -- Chapter 4. Movements from the margins : when women dance independently -- Chapter 5. An aesthetic of independence -- Chapter 6. Performing genealogies -- Chapter 7. Re-writing as gesture from elsewhere.
UCASM-2063
Keywords: Ballet -- Philippines; Feminism and dance -- Philippines -- History; Dance -- Social aspects -- Philippines